Nonwetting phase residual saturation in sand packs - Gittins, P.; Iglauer, Stefan; Pentland, C.; Al-Mansoori, S.; Al-Sayari, S.; Bijeljic, B.; Blunt, M. (Begell House, 2010)
We measure residual nonwetting phase saturation in six unconsolidated sands of different average grain sizes. Wealso analyze the pore structure using three-dimensional images from which topologically equivalent pore networks are extracted. The residual saturations range from 10.8% to 13.1%, which is lower than for most consolidated media. Higher porosity is associated with lower residual saturations, while there is little correlation between grain and pore shape and the degree of trapping. We also study layered packs: the residual saturations are reduced compared to comparable homogeneous systems. We discuss the results in the context of capillary trapping during carbon storage in aquifers.